Social factors, health policy, and environment: implications for cardiovascular disease across the globe - Lear, Scott A; McKee, Martin; Hystad, Perry; Walker, Blake Byron; Murphy, Adrianna; Brauer, Michael; Walli-Attaei, Marjan; Rosengren, Annika; Rangarajan, Sumathy; Chow, Clara K; Yusuf, Salim (European heart journal, 2025)
Graphical Abstract Graphical Abstract Abstract Cardiovascular disease (CVD) is the leading cause of deaths worldwide, with 80% occurring in low- and middle-income countries. These countries are characterized by rapid urbanization, poorly funded health systems, poor access to prevention and treatment strategies, and increasing age and a higher prevalence of chronic disease. Rapid urbanization has contributed to the significant environmental and societal changes affecting daily life habits and cardiovascular health. There is growing awareness that environmental and social exposures and policies can influence CVD directly or through behavioural risk factors. However, much of this knowledge comes from studies in high-income countries and is applied to low- and middle-income countries without evidence to indicate this is appropriate. This state-of-the-art review will present and synthesize key findings from the Prospective Urban Rural Epidemiology study and related studies that have aimed to understand the environmental, social, and policy determinants of cardiovascular health in countries across varying levels of economic development through an urban/rural lens. Emerging from these findings are future policy and research recommendations to accelerate the reduction of the global burden of CVD.